The impact of climate change on Hydrological Conditions of the Mujeb Basin, Using Incremental Climate Change Scenarios, Soil and Water Assessment Model and Geospatial Techniques - Alsharafat, Salman Ra’ad (Journal of natural sciences, life and applied sciences, 2022)
This study aimed at clarify the impact the climate change on the hydrological conditions of the Mujib Basin using the gradual scenarios method, the soil and water assessment model, and geospatial techniques (GIS) for the purposes of supporting the water management plans of the basin, making the most of the available water resources in the basin, and building a hydrological database for the basin through the availability of climatic and hydrological data available by the Jordan Meteorological Department. In addition to facing future challenges in light of potential climate change, whether it is positive towards increasing precipitation rates and the prevalence of humid conditions or negatively towards decreasing precipitation rates and thus dry conditions prevail. The study concluded that the Mujib Basin receives a rainfall rate of 119.9 mm annually, the bulk of which is lost through the evaporation process, as 61% of the total precipitation goes to waste as a result of the actual evaporation, while the surface runoff accounts for 16.6 percent of the total precipitation. on the blue basin. The study also showed that 22.4 percent of the precipitation received by the Mujib Basin goes to what is known as water yield. The study recommends the need to intensify reliance on the soil and water assessment model and geospatial techniques in the processes of surface hydrological modeling of basins, because of the effectiveness and efficiency of the results given by it in the water management of water basins, whether in the current or future reality.